Phytoextraction of copper from aqueous solution by vetiver grass [Chrysopogon zizanioides (L.) Roberty] a study on the effects of different factors - Soriano, Maria Marecris U.
Copper is primarily produced using conventional mining methods associated with an environmental problem known as acid mini drainage (AMD). This acid may leach metals as it flows and reach water bodies thereby affecting aquatic ecosystem. AMD like other wastewaters may contain metals including copper. Decontamination as well as recovery of metals from these wastewaters is a challenge and an issue that may be potentially addressed by phytomining, i.e., the use of plants to extract and produce metals. This study focuses on the early stages of phytoextraction which is a phytoremediation technique and can be considered as the first stage of phytomining. In this research, the effects of different factors such as plant age, presence of citric acid as chelating agent, copper and iron solution concentrations on the phytoextraction of copper from aqueous solution by vetiver grass were investigated. A 7-day hydroponic study in parametric and full factorial designs were conducted. Results showed that higher copper concentration in solution led to lower bioconcentration factor and higher total copper uptake in vetiver grass. Overall, young vetiver grass hand higher decrease in biomass, total copper uptake and bioconcentration factor than mature ones. At 7.5 ppm iron, the copper translocation factors in vetiver grass were significantly deceased. Expect in vetiver grass grown in solution with 3,000 ppm copper, most of the translocation were less than 1. It was also found out that citric acid significantly alleviated copper phytotoxicity symptoms in vetiver grass.